Far from Home: Life as an LGBT migrant in Ireland - Keogh, Brian (National LGBT Federation, 2018)
Data from Burning Issues 2, Ireland’s largest national consultation of the LGBT community to date, suggested that more needs to be done to make Ireland a welcoming place for LGBT migrants.To explore this issue further, the National LGBT Federation sought and received funding from the Community Foundation for Ireland to carry out research on the experiences and needs of LGBT migrants in Ireland.The research element of this project was designed in collaboration with a diverse group of people who have migrated to Ireland and identify as LGBT.A survey with a mix of open and closed questions was distributed online and 231 people contributed to this project by completing it. A wide range of nationalities were represented, with participants from 48 different countries. The most commonly represented countries were Brazil, the US, Poland, the UK and Germany. Twelve participants were living in direct provision centres at the time. Roughly 90% of participants identified as cisgender (205), with 10% identifying as transgender (20). They shared their experiences of coming to Ireland, making social connections, stigma, integration and acceptance. The participants also discussed their health, the level of opportunity they felt they had in Ireland, and whether they planned to stay long-term.
PUBLISHED
Keywords: LGBT; Migrants; Social connections; Stigma; Integration; Acceptance